Industry Competition and Performance Persistence in Brazilian Equity Mutual Funds - Sabrina Espinele da Silva; Leticia Fernandes Pereira; Simone Evangelista Fonseca; Robert Iquiapaza (BBR: Brazilian Business Review)
The Brazilian mutual fund industry, despite having a high increase in net worth, is concentrated around a few large administrators. Therefore, it is worth questioning the extent to which this level of concentration can affect the performance delivered to the shareholders, as greater concentration implies less competition. In this way, this research aimed to analyze the impact of market competition on the performance persistence of equity mutual funds in Brazil. Using a sample of free portfolio equity investment funds from 2010 to 2019, the main results point to the existence of performance persistence for Brazilian free portfolio equity funds. Furthermore, they pointed out a positive and statistically significant relationship between the level of competition and the performance of funds, as well as in the interaction between competition and performance persistence. Consequently, indicating that, funds with greater performance persistence tend to maintain this persistence even in the face of greater industry competition.